2013
DOI: 10.3389/fphys.2013.00254
|View full text |Cite
|
Sign up to set email alerts
|

Identifying potential functional impact of mutations and polymorphisms: linking heart failure, increased risk of arrhythmias and sudden cardiac death

Abstract: Researchers and clinicians have discovered several important concepts regarding the mechanisms responsible for increased risk of arrhythmias, heart failure, and sudden cardiac death. One major step in defining the molecular basis of normal and abnormal cardiac electrical behavior has been the identification of single mutations that greatly increase the risk for arrhythmias and sudden cardiac death by changing channel-gating characteristics. Indeed, mutations in several genes encoding ion channels, such as SCN5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 112 publications
0
14
0
Order By: Relevance
“…In one study investigating the consequences of K V 4.3 overexpression on Na V 1.5 current and consequent sodium channel availability, the authors concluded that the current of the Na V 1.5 protein was directly impacted by several factors, including the gain-of-function of the K V 4.3 protein encoded for by the KCND3 gene [62]. It has been suggested that post-translational modifications, such as a defect in the splicing process [93] or trafficking [94,95], or a modification in phosphorylation, methylation, or acetylation [96], could explain alterations in the function of the channel encoded by SCN5A in the absence of mutations in this gene itself. Also, the predicted phenotypic effect of a particular variant should take into consideration that ancestry can affect the pathogenicity of a particular variant [97].…”
Section: Sodium Channel Mutationsmentioning
confidence: 99%
“…In one study investigating the consequences of K V 4.3 overexpression on Na V 1.5 current and consequent sodium channel availability, the authors concluded that the current of the Na V 1.5 protein was directly impacted by several factors, including the gain-of-function of the K V 4.3 protein encoded for by the KCND3 gene [62]. It has been suggested that post-translational modifications, such as a defect in the splicing process [93] or trafficking [94,95], or a modification in phosphorylation, methylation, or acetylation [96], could explain alterations in the function of the channel encoded by SCN5A in the absence of mutations in this gene itself. Also, the predicted phenotypic effect of a particular variant should take into consideration that ancestry can affect the pathogenicity of a particular variant [97].…”
Section: Sodium Channel Mutationsmentioning
confidence: 99%
“…A number of mutations on SCN5A gene lead to dysregulation of Na v 1.5 trafficking to the surface membrane resulting in reduced Na + current amplitude [47]. In this case, use of Na v 1.5 activators appears to be a promising prospective as they could compensate for the loss of Na + permeability and possibly restore cardiac function.…”
Section: Na V Channel Activatorsmentioning
confidence: 99%
“…Variants of LQTS may contribute to susceptibility for diTdP in a percentage on average around 5-10% of subjects. Identification of these cases emphasizes the emerging role of preventive medicine [47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Congenital Long Qt Syndromes Antipsychotics and Sudden Cardmentioning
confidence: 99%